1983
DOI: 10.1139/z83-239
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of nuclear polyhedrosis virus produced in field populations of the European pine sawfly, Neodiprion sertifer (Geoff.) (Hymenoptera: Diprionidae)

Abstract: KAUPP, W. J. 1983. Estimation of nuclear polyhedrosis virus produced in field populations of the European pine sawfly, Neodiprion sertifer (Geoff.) (Hymenoptera: Diprionidae). Can. J. Zool. 61: 1857-1861. The quantity of virus measured as the number of polyhedral inclusion bodies (PIBs) produced and liberated at death from two diseased European pine sawfly (Neodiprion sertifer (Geoff.)) populations was studied over a 3-year period in Britain. As high as 2.3 X 1015 PIBsIha were produced as a resut of a natural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Regardless of the mechanism, the result that late instars are both more infectious and more likely to become infected indicates that, in epizootics in natural populations, infection rates should be highest among late instars. This is indeed true in naturally occurring virus epizootics in many Lepidoptera (and diprionid Hymenoptera [sawflies]) (Kaupp 1983, Tanada 1985, Woods and Elkinton 1987 including DFTM (Mason andThompson 1971, Mason 1981), although often there is a peak of infection in the first instar due to the overwinter survival of virus on contaminated eggs (Murray and Elkinton 1989). This correspondence between the results of my experiments and observations of naturally occurring epizootics suggests that my results are not peculiar to my small experimental arenas.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Regardless of the mechanism, the result that late instars are both more infectious and more likely to become infected indicates that, in epizootics in natural populations, infection rates should be highest among late instars. This is indeed true in naturally occurring virus epizootics in many Lepidoptera (and diprionid Hymenoptera [sawflies]) (Kaupp 1983, Tanada 1985, Woods and Elkinton 1987 including DFTM (Mason andThompson 1971, Mason 1981), although often there is a peak of infection in the first instar due to the overwinter survival of virus on contaminated eggs (Murray and Elkinton 1989). This correspondence between the results of my experiments and observations of naturally occurring epizootics suggests that my results are not peculiar to my small experimental arenas.…”
Section: Discussionsupporting
confidence: 62%
“…This phenomenon is sometimes interpreted to mean that healthy late instars in the field are less likely to become infected with the disease (Entwistle et al 1983, Tanada 1985, Watanabe 1987. Second, infectiousness, as measured by the number of virus particles produced by an infected host, increases with instar ( Thompson and Scott 1979, Kaupp 1983, Teakle and Byrne 1989. This has likewise been interpreted to mean that infected late instars in the field are more likely to transmit the disease.…”
Section: Introductionmentioning
confidence: 99%
“…The model thus ignores much of what biologists have discovered can influence the course of a virus disease in an individual host. For example, host stage can affect the susceptibility (Watanabe 1987;Hochberg 1991) and infectiousness (Thompson & Scott 1979;Kaupp 1983; Teakle & Byrne 1989; Dwyer 1991a) of individual hosts. Chemical constituents of foliage consumed by hosts also can affect the susceptibility of individual hosts (Keating & Yendol 1987;Keating, McCarthy & Yendol 1990).…”
Section: Ds D = R(s + I)-vps Eqn 1 Dt Di -= Vps-(x( + B)i Eqn 2 Dp -=mentioning
confidence: 99%
“…Epizootics of NeabNPV occur at peak balsam fir sawfly population outbreak densities [ 10 , 13 ], but it is not clear how NeabNPV epizootics are initiated and transmitted throughout balsam fir sawfly populations. Other studies on NPV transmission in sawflies have shown that epizootics are initiated from persistent environmental contamination with OBs [ 22 , 23 , 24 , 25 , 26 , 27 ] and subsequent spread from groups of sawfly larvae within a tree and from tree to tree [ 28 , 29 , 30 ]. The current study demonstrates how a NeabNPV epizootic might begin in balsam fir sawfly populations with the initial infection of low numbers of balsam fir sawfly larvae in isolated groups.…”
Section: Resultsmentioning
confidence: 99%